Influence of curcumin on the pharmacodynamics and pharmacokinetics of gliclazide in animal models - Vatsavai, Leela Krishna (J Exp Pharmacol, 2016)
PURPOSE: Patients suffering from obesity-related diseases use multiple prescription drugs to control their condition, and it is therefore essential to determine the safety and efficacy of any combination. Gliclazide is one of the most commonly used drug of choice for treatment of type 2 diabetes, and curcumin is a widely used herbal supplement to counter obesity condition. The objective of this study was to investigate the effect of oral administration of curcumin on pharmacodynamics and pharmacokinetics of gliclazide in rats and rabbits to further evaluate the safety and effectiveness of this combination. METHODS: Influence of curcumin on the activity of gliclazide was determined by conducting single- and multiple-dose interaction studies in rats (normal and diabetic) and rabbits. Blood samples collected at predetermined time intervals from experimental animals were used for the estimation of glucose and insulin levels by using automated clinical chemistry analyzer and radioimmunoassay method, respectively. The insulin resistance and β-cell function were determined by homeostasis model assessment. Additionally, serum gliclazide levels in rabbits were analyzed by high-performance liquid chromatography. RESULTS: Gliclazide showed peak reduction in blood glucose levels at 2 and 8 hours in rats and at 3 hours in rabbits. This activity of gliclazide was not altered by single-dose treatment with curcumin. However, in multiple-dose interaction studies, samples analyzed from all time points showed subtle but significantly greater reduction in percent blood glucose ranging from 23.38% to 42.36% in normal rats, 27.63% to 42.27% in diabetic rats, and 16.50% to 37.88% in rabbits. The pharmacokinetics of gliclazide was not altered by single- or multiple-dose curcumin treatments in rabbits. CONCLUSION: The interaction of curcumin with gliclazide up on multiple-dose treatment was pharmacodynamic in nature, indicating the need for periodic monitoring of glucose levels and dose adjustment as necessary when this combination is prescribed to obese patients.